SCREENING FOR ANTIBACTERIAL PROPERTIES OF THREE MEDICINAL PLANTS AGAINST SALMONELLA SP. ISOLATES OBTAINED FROM BROILER CARCASS IN INDONESIA - Poeloengan, M.; Andriani, A. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
Antibacterial properties of three medicinal plants used widely amongst the native Indonesians, i.e.,sirih (Piper betel), garlic (Allium sativum) and jinten hitam (Nigella sativa) were screened and evaluatedagainst Salmonella sp. isolates. For this purpose, the three plants’ powder, aqueous and ethanol extractswere prepared. The tests’ results demonstrated the three plants’ anti Salmonella sp. activities. In thisconjunction, the aqueous extract of Allium sativum, the ethanol extracts of Nigella sativa, and Piperbetel, consecutively produced 17 mm, 15 mm and 13 mm diameter of bacterial growth inhibition zones.As a comparison, sensitivity tests of three commercial antibiotics, i.e., chloramphenicol, tetracycline,and gentamycin on Salmonella sp. isolates produced 19.7-27.3 mm growth inhibition zones. Garlichaving antimicrobial potential was comparable to the commercial antibiotics, can be used as adecontaminant against Salmonella sp. to maintain the quality of the broiler carcasses and thereforeprolonging the carcass shelf-life.